2015
DOI: 10.1155/2015/147173
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Loop-Mediated Isothermal Amplification for the Detection of Leptospira

Abstract: Leptospirosis is a worldwide zoonosis caused by an infection with the pathogenic species of Leptospira. We have developed a loop-mediated isothermal amplification (LAMP) assay to detect the DNA of Leptospira spp. Six sets of primers targeting the gene of the subsurface protein, lipL32, were evaluated for their detection sensitivity. The best primer set detected less than 25 copies of lipL32 per reaction of both plasmid DNA template and purified leptospiral genomic DNA. By combining primers targeting lipL32 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…Primer sets for the LAMP assay include the forward outer primer (F3), the backward outer primer (B3), the forward inner primer (FIP), the backward inner primer (BIP), and two other primers designed to accelerate the amplification, including the forward loop primer (LF) and the backward loop primer (LB). With the primers in hand, the LAMP assay can be performed with simple and readily available incubation sources like a water bath or heating block for isothermal heating [35,54,55].…”
Section: Principles Of Lamp Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Primer sets for the LAMP assay include the forward outer primer (F3), the backward outer primer (B3), the forward inner primer (FIP), the backward inner primer (BIP), and two other primers designed to accelerate the amplification, including the forward loop primer (LF) and the backward loop primer (LB). With the primers in hand, the LAMP assay can be performed with simple and readily available incubation sources like a water bath or heating block for isothermal heating [35,54,55].…”
Section: Principles Of Lamp Assaymentioning
confidence: 99%
“…Viruses 2019, 11, x FOR PEER REVIEW 2 of 20 backward loop primer (LB). With the primers in hand, the LAMP assay can be performed with simple and readily available incubation sources like a water bath or heating block for isothermal heating [35,54,55]. During the initial stages of the LAMP reaction, the inner primers (FIP or BIP) anneal to regions F2c or B2c within the target region.…”
Section: Principles Of Lamp Assaymentioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) assays for Leptospira have been of interest for this purpose, as these do not require real-time PCR instruments [38]. Chen et al (2015) and Nurul Najian et al (2016) reported the design and analytical evaluation of two new LAMP assays for pathogenic Leptospira [32,33]. Both assays target lipL32 , while the assay by Chen et al includes lipL41 as a second target.…”
Section: Molecular Diagnostics For Leptospirosismentioning
confidence: 99%
“…Both assays target lipL32 , while the assay by Chen et al includes lipL41 as a second target. Both tests demonstrated good analytical performance; however neither publication included a clinical evaluation [32,33]. …”
Section: Molecular Diagnostics For Leptospirosismentioning
confidence: 99%
“…A combination of primer sets targeting lipL32 and lipL41 genes for Leptospira spp. detection of human specimens, shows positive results with PCR Leptospira –positive samples which are classified into three species including L. interrogans , L. borgpetersenii and L. weilii [ 5 ]. The study of Koizumi et al .…”
mentioning
confidence: 99%